Security Enhancement in Networked Embedded System - Pradip Ram Selokar; P T Karule (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In the developed system ARM9 is a master and Two ARM7s are slaves. The peripherals are being controlled by two ARM7 boards. The Peripherals are connected to the ARM7 through Complex Programmable Logic Device (CPLD). The CPLD is in turn connected to the ARM7 using Serial Peripheral Interface (SPI). The ARM7 boards collect the information from the peripherals and send it to the ARM9 board. The communication between ARM7 and ARM9 is via UART (Universal Asynchronous Receiver Transmitter) over CAN (Controller Area Network). The ARM9 board has got the software intelligence. The ARM9 behaves as a master and two ARM7 boards behave as slaves. Being master ARM9 passes tokens to ARM7 which in turn returns (Acknowledges) the token. The ARM9 is further connected to Proxy via Ethernet. The proxy is further connected to the service platform (server) via Ethernet. So subsequently any decisions at any stage can be changed at server level. Further these commands can be passed on to ARM9 which in turn controls the peripherals through ARM7. (a) The system which we have developed consists of ARM9 as a master, Two ARM7 as Slaves. The communication between ARM9-ARM7 is via UART over a CAN, (b) Each ARM7 further communicates serially (RS232) with the two 8051 Microcontroller nodes, (c)Thus a networked Embedded System is developed wherein the serial data is brought over Ethernet. The ARM7 board, which is directly linked with the peripherals, can be modified of its functionality as and when required. The functionality of ARM7 can be modified by upgrading its firmware. To upgrade the firmware same communication link has been used. ARM7 receives the new firmware via same ARM9-ARM7 communication link. The Flash Write operation is performed using the source code to write the new firmware. Bootloader application for the ARM7 has been developed. The signature has been incorporated to assure authenticity of the new Firmware. Intel Hex File Format is used to parse the hex file.